Trade Liberalisation Could Improve Producers Profitability in Agriculture: A Case of Basmati Rice. (The Pakistan Development Review, 2009)
This peace of research has been conducted, as part of PhD research of the first author, with the objectives to (i) identify various protection policies and interventions exercised in Basmati rice economy in Pakistan (ii) estimate welfare effects associated with existing protection policies and (iii) to estimate implications of WTO’s trade liberalisation in domestic economy and foreign markets. The quantitative analysis of data reveals that Basmati rice crop hanged about ‘price tax-cum-export tax’ regime during the study period. Welfare analysis of such policy interventions estimated higher losses to producers (Pak Rs 657.95 million per year) than gains to consumers (Rs 448.76 million per year) during pre-WTO period. The same trend continued during post-WTO period but producers’ losses were comparatively smaller i.e., 649.48 million per year. In case of free trade, simulation results demonstrate greater gains to producers than losses to consumers. If world market was liberalised, supplementary gains in the range of Rs 276.65 million to Rs 451.60 million per year during earlier and Rs 333.45 million to Rs 637.40 million per year during the later period would have occurred at domestic level. In light of analytical results, the following recommendations are made. (i) Government needs to curtail interventions in Basmati rice economy. (ii) Besides, improving the pace of trade liberalisation at domestic level, Pakistan should pursue with other members in WTO’s negotiations for early implementation of WTO’s trade liberalisation on international level. (iii) Government of Pakistan should gear up its efforts as facilitator of trade in accordance with WTO agreements and increase investment in areas of research, development, and out-reach. JEL classification: Q17, Q18, Q28 Keywords: Basmati Rice, Government Intervention, Welfare Effect, Trade Liberalisation, WTO.